Development of a system for the glucose level in the blood monitoring - Anisimov, A. A.; Grigorash, A. (Proceedings of the 2014 IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference : 3-5 February 2014, 2014)
This paper describes design flow of both wireless platform and software for continuous monitoring of glucose level in blood. The biosensor which measures the glucose level in the blood is implanted under the patient's skin. The transmission of physiological data and power for the biosensor operation is made with the use of RFID technology, which allows to reduce dimensions of the sensor and extend its life substantially. The developed system allows to receive a signal from the sensor, perform its primary processing and to transmit data to the target device (PC, smartphone, tablet, etc) using Bluetooth interface.